Validation and analysis of expression, prognosis and immune infiltration of WNT gene family in non-small cell lung cancer - Wang, Jianglin; Yang, Qingping; Tang, Mengjie; Liu, Wei (Frontiers in Oncology, 2022)
Early diagnosis and prognosis prediction of non-small cell lung cancer (NSCLC) have been challenging. Signaling cascades involving the Wingless-type (WNT) gene family play important biological roles and show prognostic value in various cancers, including NSCLC. On this basis, this study aimed to investigate the significance of WNTs in the prognosis and tumor immunity in NSCLC by comprehensive analysis. Expression and methylation levels of WNTs were obtained from the ONCOMINE, TIMER, and UALCAN. The dataset obtained from The Cancer Genome Atlas (TCGA) was utilized for prognostic analysis. cBioPortal was used to perform genetic alterations and correlation analysis of WNTs. R software was employed for functional enrichment and pathway analysis, partial statistics, and graph drawing. TRRUST was used to find key transcription factors. GEPIA was utilized for the analysis of expression, pathological staging, etc. Correlative analysis of immune infiltrates from TIMER. TISIDB was used for further immune infiltration validation analysis. Compared with that of normal tissues, WNT2/2B/3A/4/7A/9A/9B/11 expressions decreased, while WNT3/5B/6/7B/8B/10A/10B/16 expressions increased in lung adenocarcinoma (LUAD); WNT2/3A/7A/11 expressions were lessened, while WNT2B/3/5A/5B/6/7B/10A/10B/16 expressions were enhanced in squamous cell lung cancer (LUSC). Survival analysis revealed that highly expressed WNT2B and lowly expressed WNT7A predicted better prognostic outcomes in LUAD and LUSC. In the study of immune infiltration levels, WNT2, WNT9B, and WNT10A were positively correlated with six immune cells in LUAD; WNT1, WNT2, and WNT9B were positively correlated with six immune cells in LUSC, while WNT7B was negatively correlated. Our study indicated that WNT2B and WNT7A might have prognostic value in LUAD, and both of them might be important prognostic factors in LUSC and correlated to immune cell infiltration in LUAD and LUSC to a certain extent. Considering the prognostic value of WNT2B and WNT7A in NSCLC, we validated their mRNA and protein expression levels in NSCLC by performing qRT-PCR, western blot, and immunohistochemical staining on NSCLC pathological tissues and cell lines. This study may provide some direction for the subsequent exploration of the prognostic value of the WNTs and their role as biomarkers in NSCLC.